DETERMINATION OF TANNINS IN ALCOHOL-CONTAINING LIQUIDS - Irina L. Kazantseva (Теория и практика судебной экспертизы)
The paper presents experimental findings on the influence of caramel color on the UV absorption spectra of tannin-containing liquids. The presence of caramel color in alcohol-containing brandy-type liquids is demonstrated to affect optical density at 280 nm, and therefore the results of spectrophotometric determination of tannins in brandies. A comprehensive approach incorporating a range of techniques, suсh as chemical testing for tannins, UV absorption spectroscopy, and quantitative permanganometric determination of tannins, is shown to be appropriate for the study of phenolic compounds.